Mechanistic evaluation of asphaltic pavement based on Benkelman Beam Deflection - Buhari, Rosnawati (2003)
When empirical evaluation of pavement layers overlay was practiced, the selection of layer thickness and properties was made without benefit of mechanistic analysis. The application of elastic theory to the design of overlays on existing pavement requires that the modulus of elasticity be assigned to the existing structural system. Elastic moduli are determent from pavement surface deflection. Benkelman Beam conducted under WASHO method to collect data in order to find deflection condition of existing pavement. Based on present study, graphical method which deflection dependent was developed to determine parameters of elasticity. The objective of the present study are to find out the elastic/stiffness modulus parameters for the layer of asphaltic pavement by using Benkelman beam deflection and compare the remaining life of the existing pavement and to propose overlay thickness based on conventional and mechanistic analysis approach. As the conclusion, from the analysis I have determined that the elastic modulus can obtained by interpretation of Benkelman Beam deflection test also have proved that the mechanistic analysis is the available evaluation for existing pavement.